Konseling Individu Dengan Teknik Penguatan Positif Dalam Meningkatkan Keterampilan Sosial Anak Di Panti Asuhan Aisyiyah Al-Munawaroh Kota Prabumulih - Aulia, Fifin Indah; jannati, zhila; suryati, Suryati (BKI IAIN Pontianak, 2023)
Abstract: Social skills are very important for every individual in order to establish good relationships with others. The purpose of this study was to find out the description before carrying out individual counseling with positive reinforcement techniques to improve children's social skills at the Aisyiyah Al-Munawaroh Prabumulih Orphanage, to find out how the implementation of individual counseling with positive reinforcement techniques in improving social skills in children at the Aisyiyah Al-Munawaroh Orphanage Prabumulih, and finally knowing what the picture is after individual counseling with positive reinforcement techniques for children's social skills at the Aisyiyah Al-Munawaroh Prabumulih Orphanage. This study uses a qualitative descriptive research method. The subjects of this study were three people, namely PA, RC and WS clients. Data collection techniques used are observation, interviews, and documentation. While the data analysis techniques used data reduction, data presentation and conclusions. The results of this study showed that prior to counseling the three subjects showed that they were still at a low level of social skills such as experiencing insecurity, being introverted such as limiting themselves to being open with whom, finding it difficult to mingle and starting to interact with people around them, not being able to understand feelings of others or empathy. The implementation of individual counseling is carried out in six meetings with three stages, namely the initial stage, the work stage, and the final stage. The picture after carrying out individual counseling with positive reinforcement techniques, the subject has undergone changes, starting to dare to try to mingle or adapt with other people and friends, starting to interact with people around him, being able to empathize or getting better at understanding the feelings of others, and starting to apply and obey the rules rules at the orphanage and at school.